Aggressive variant large granular lymphocytic leukaemia: a case report - Md Noor, Sabariah; Seman, Zainina; Idris, Faridah; Leong, Chooi Fun (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Clonal disorders of LGL may either be CD3+ CD56- or CD3- CD56+ phenotype and these have been designated as T-cell leukaemia (T-LGL) or natural killer cell (NK)-LGL leukaemia respectively. Clonality is usually demonstrated by clonal rearrangement of T-cell receptor gene rearrangement or identified by flowcytometry analysis. Most patients with T-LGL will have an indolent course. In this report we described an aggressiveness of disease in a patient with clonal CD3+ LGL leukaemia whose cells also co-expressed CD56 diagnosed by flowcytometry. The patient responded well to interrupt all standard risk protocol however succumbed to her disease while waiting for upfront stem cell transplant. This case highlights on both the classical laboratory findings of rare entity of disease as well as a review of the literature pertaining particularly on its management.